Wireless capsule endoscopy in enteropathy induced by nonsteroidal anti-inflammatory drugs in pigs - Tachecí, Ilja; Kvetina, Jaroslav; Bures, Jan; Osterreicher, Jan; Kunes, Martin; Pejchal, Jaroslav; Rejchrt, Stanislav; Spelda, Stanislav; Kopácová, Marcela (Digestive diseases and sciences, 2010)
AIM: The aim of this study is to evaluate the diagnostic yield of capsule endoscopy in nonsteroidal anti-inflammatory drug (NSAID)-induced enteropathy in pigs. MATERIALS AND METHODS: Indomethacin (400 mg/day) was administrated orally for 10 days to eight female pigs weighing 36.3+/-2.4 kg. Afterwards, capsule endoscopy was performed, using the EndoCapsule system (Olympus Optical Co., Tokyo, Japan). The following morning, pharmacological euthanasia and immediate autopsy were performed. RESULTS: Small bowel injury compatible with NSAID-induced enteropathy was observed in 7/8 animals. The most common lesions were red spots and erosions. Ulcers and small intestinal bleeding were identified sporadically. Sensitivity and specificity of capsule endoscopy were 83.3% and 95.8%, respectively. CONCLUSION: Our results indicate that wireless capsule endoscopy is a highly accurate noninvasive method for evaluation of experimental NSAID-induced enteropathy.
Keywords: modely nemocí na zvířatech; Sus scrofa; Capsule Endoscopy; Intestine, Small; Indomethacin; střevní sliznice; Peptic Ulcer Hemorrhage; krvácení z peptického vředu; dvanáctníkové vředy; Intestinal Diseases; Predictive Value of Tests; kapslová endoskopie; ileum; jejunum; antiflogistika nesteroidní; Anti-Inflammatory Agents, Non-Steroidal; Animals; ženské pohlaví; Ileum; Duodenum; zvířata; Intestinal Mucosa; Jejunum; Sensitivity and Specificity; senzitivita a specificita; Disease Models, Animal; tenké střevo; prediktivní hodnota testů; nemoci střev; indomethacin; Female; Duodenal Ulcer; duodenum